In vitro induction of regulatory T cells by anti-CD3 antibody in humans - Abraham, Michal (2008)
Therapy with anti-CD3 antibody is effective in controlling models of autoimmune diseases and can reverse or prevent rejection of grafts. We studied the in vitro immunomodulatory effect of anti-CD3 treated human T cells. CD4(+) T cells were stimulated with plate bound anti-CD3 and cultured for 12 days after which they were cultured with autologous peripheral blood mononuclear cells (PBMCs) and stimulated with soluble anti-CD3. We found that CD4(+) T cells that were stimulated with anti-CD3 (T(αCD3)) markedly suppressed the proliferation and cytokine production of autologous PBMCs. These regulatory T cells were not induced by incubation with isotype control (T(Control)) antibody or when anti-CD3 was combined with high doses of anti- CD28 (T(αCD3/CD28)). T(αCD3) regulatory cells were anergic and produced lower levels of IFN-γ, TNF-α and IL-2, and higher levels of TGF-β than T(Control) or T(αCD3/CD28) .There were no differences in the expression of CD25, CD45RB or CTLA-4 on T(αCD3) as compared to T(Control) or T(αCD3/CD28) and CD4(+) CD25(−) T(αCD3) cells were identical to CD4(+) CD25(+) T(αCD3) cells in their in vitro suppressive properties. Recombinant IL-2 in vitro abrogated the suppressive effect of T(αCD3). The suppressive effect was not related to apoptosis, was independent of HLA since T(αCD3) also suppressed allogeneic PBMCs, and was not related to soluble factors. Finally, no suppression was observed when non T cells were removed from culture or when cultures were stimulated with plate bound anti-CD3, consistent with the ability of T(αCD3) to downregulate CD80 on dendritic cells in co-culture experiments. Thus, we have identified human T cells with strong in vitro regulatory properties induced in vitro by anti-CD3 which appear to act in a non-HLA restricted fashion by affecting antigen presenting cells.